Labour Market Dualism and the Heterogeneous Wage Gap for Temporary Employment. A Multilevel Study across 30 Countries - Sophia Fauser; Michael Gebel (Luxembourg Income Study (LIS), 2023)
This study investigates the hourly wage gap between 25-55 year old temporary and permanent employees across 30 countries worldwide based on Luxembourg Income Study data from 2000-2019 supplemented by other survey data. Two-stage multilevel regressions reveal wage disadvantages for temporary workers, particularly for prime-age workers and those working in medium/high-level occupations. There is no evidence that a stronger institutional dualization in terms of stronger employment protection for permanent contracts increases the wage gap. Instead partial deregulation matters: In countries where permanent workers are strongly protected the wage gap is larger if the use of temporary contracts is deregulated. Moreover, results suggest that the larger the size of the temporary employment segment the larger the wage gap. Thus, our findings indicate that stronger institutional and structural labour market dualism amplify labour market inequality in terms of wage gaps between temporary and permanent workers.
Keywords: J31; J41; J42; 330; contracts; flexibility; wages; segmentation; labour market institutions